2022
DOI: 10.1111/nhs.12985
|View full text |Cite
|
Sign up to set email alerts
|

The impact of facemasks on blood donation process: The professionals' perspective

Abstract: Facemasks represent an essential measure of prevention against the spread of COVID-19; however, they lessen the ability to convey and understand emotions through facial expressions. In blood donation settings, facemasks may interfere with professionals' tasks. This qualitative study aims to describe healthcare staff's experiences, beliefs, and attitudes toward facemask wearing and strategies used to overcome communication and relational barriers along the blood donation process.Semistructured qualitative inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…In addition to the operational issues above, major changes to donation environment and operation policies could contribute to the significant year effects identified in both the first-time and the repeat donation models. One good example was the implementation of COVID-19 restriction measures in blood donation settings, of which facemask wearing could influence breathing, effective communication, and ability to detect early signs of adverse reactions ( 25 , 30 ), generate hypercapnia or related issues, and subsequently elevate iVVR rates roundly ( Figure 3 ). As a matter of fact, the COVID-19 pandemic itself could have generated certain anxiety to donors contributing to the increase of iVVR rates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the operational issues above, major changes to donation environment and operation policies could contribute to the significant year effects identified in both the first-time and the repeat donation models. One good example was the implementation of COVID-19 restriction measures in blood donation settings, of which facemask wearing could influence breathing, effective communication, and ability to detect early signs of adverse reactions ( 25 , 30 ), generate hypercapnia or related issues, and subsequently elevate iVVR rates roundly ( Figure 3 ). As a matter of fact, the COVID-19 pandemic itself could have generated certain anxiety to donors contributing to the increase of iVVR rates.…”
Section: Discussionmentioning
confidence: 99%
“…Further research is needed to address a few shortfalls. Firstly, major donation environmental changes like implementation of interventions ( 24 ) and the COVID-19 pandemic ( 25 ) could influence risk patterns of VVRs, which is yet to be assessed. Secondly, the identified VVR risk factors may not only carry additive main effects but also interact with each other ( 15 , 16 ) yielding non-additive interactive effects that are yet to be characterized.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, RNs with more years of experience experienced a deterioration in their relationships with patients and an impoverishment in the quality of communication, generated by the implementation of face masks in the clinical setting. Healthcare professionals indicated that the use of face masks altered their ability to identify facial expressions, recognize patients' faces when not wearing face masks, difficulty in expressing and identifying emotions, and a decrease in their empathic skills, constituting a challenge for relationships with patients (Bani et al, 2022). As a result, they must go through a transition process to modify their routine way of communicating and adapt to this new situation.…”
Section: Discussionmentioning
confidence: 99%
“…While wearing facemasks has been useful in reducing the spread of viruses, it can have a negative effect on the communication taking place between health care professionals and their patients. Research shows that the wearing of facemasks has hampered the health care professionals’ ability to build empathic relationships because it interferes with accurate nonverbal communication of emotions through facial expressions (Bani et al, 2022a; Bani et al, 2022b).…”
Section: Discussionmentioning
confidence: 99%